Fennoscandian tree-ring anatomy shows a warmer modern than medieval climate ... - Jesper, Björklund; Kristina, Seftigen; Markus, Stoffel; Fonti Marina, V.; Kottlow Sven; Frank David, C.; Jan, Esper; Patrick, Fonti; Hugues, Goosse; Håkan, Grudd; Gunnarson Björn, E.; Nievergelt Daniel; et al. (Zenodo, 2023)
This repository contains the Matlab scripts used in the article Björklund et al 2023. Fennoscandian tree-ring anatomy shows a warmer modern than medieval climate. Nature. DOI 10.1038/s41586-023-06176-4 URL: https://www.nature.com/articles/s41586-023-06176-4 Investigators: Jesper Björklund, Kristina Seftigen, Markus Stoffel, Marina V. Fonti, Sven Kottlow, David C. Frank, Jan Esper, Patrick Fonti, Hugues Goosse, Håkan Grudd, Björn E. Gunnarson, Daniel Nievergelt, Elena Pellizzari, Marco Carrer & Georg von Arx The Workflow folder Workflow_Björklund_etal_2023_Nature.zip contains all the necessary notes, codes and data to reproduce Main Figures 2, 3, 4 and Extended Data Figures belonging to the Article. The raw data and most of the processed data can be accessed directly through Source Data, and underlying data files to reproduce analyses and figures, or through the Matlab codes calling source data and raw data included in the folder. The Matlab working environment is necessary to operate the Matlab codes. ...